Transportation statistics that can contribute to policies and social infrastructure development aimed at ensuring the healthy growth of cities and providing support for smooth economic activity. (July 2015) - Akimura, Seiichiro
Abstract This paper aims to discuss the use of city- and transportation-related statistics in the formulation of transportation policies, focusing primarily on ensuring the healthy growth of cities and providing support for smooth economic activity in developing countries. For governments in developing and newly industrialized Asian countries, alleviating road traffic congestion represents one of the most pressing transportation policy needs. In Indonesia, for example, measures aimed at combating road traffic congestion in Jakarta were a key issue in last year's presidential elections. After detailing the close relationship between cities and transportation, this paper uses several case studies to explain the different statistical standards in developed, newly industrialized, and developing countries. The paper then discusses the statistics and analysis methods that play roles in proposing and evaluating policies and looks at the optimal performance indicators and statistics for policies, using case studies to offer concrete examples.